Editorial - Ann-Kristin Kölln; Antony Mason; Jörg Tremmel; Markus Rutsche; Maria Lenk (Intergenerational Justice Review)
In April 2019, Greta Thunberg made TIME Magazine’s 100 Most Influential People of 2019 list. The 16 year-old climate activist, who has also been nominated for a Nobel Peace Prize, started a movement that saw a multitude of student protests and school strikes around the world centred on action against climate change. TIME Magazine quoted her saying, “We can’t save the world by playing by the rules, because the rules have to be changed.” With her engagement, Thunberg inspired thousands of youth activists to join her in her efforts and has thus put not only climate change on the political agenda but also the political participation and representation of the young. And this even though Thunberg and many of her fellow protesters do not yet enjoy (full) voting rights in their respective countries. Just like the previous issue of the Intergenerational Justice Review, this one is also dedicated to the topic of the underrepresentation of younger people in political decision-making. The first two contributions in this issue pay particular attention to the existence – or lack thereof – of networks and contacts in politics that seem to be important for political representation. Daniel Stockemer and Aksel Sundström’s article titled “Youth’s underrepresentation in the European Parliament: Insights from interviews with young Members of the European Parliament (MEPs)” reports results from qualitative interviews with 23 MEPs on the factors contributing to the success and failure of young people to enter the European Parliament. They find that, in general, three common themes or complaints amongst the successful young MEPs, irrespective of their party affiliation: “(1) a general reluctance within parties to nominate young candidates, (2) young candidates lacking the necessary contacts in parties to get elected, and (3) young candidates having too little experience to gain nomination for an electable seat.” Despite these heavy criticisms of established politicians and (party) structures, the authors also summarise some more hopeful suggestions by respondents centring around the role of party youth organisations. The second contribution, by Emilien Paulis, also highlights the important role of networks and contacts, yet already at an earlier stage: when joining a political party. Drawing on social network and political participation theory and novel survey data from Belgium, Paulis explores what network patterns contribute to young people’s enrolment in a political party. He discovers strong social ties between young party members and suggests that this indicates “a certain exclusivity in recruitment patterns of political parties”. In addition, his analysis also points out that a highly homogenous network composition is a statistically significant predictor of joining a political party. Overall, Paulis, similar to Stockemer and Sundström, suggests a review of institutional processes and structures within established political organisations such as parties in order to promote a more diverse and above all younger profile of politically active citizens. The final contribution in this issue offers insights from an online survey conducted among young adults in Germany suggesting that these respondents were indeed politically interested and felt willing to assume responsibility through participation. As a consequence, Philipp Köbe concludes from his analysis that the supply-side of political organisations is the main problem in the underrepresentation and not so much young people’s lack of engagement. His four specific recommendations to political organisations follow very much from this conclusion: (1) providing transparent and suitable information to meet young people’s interests and demands; (2) lowering the electoral threshold for parties’ parliamentary representation to improve the representation of minority opinions; (3) expanding youth-friendly opportunities for political participation such as video conferences and social media usages in order to reach out to the appropriate groups; (4) improving the efficiency and impact of political decision-making to reward political engagement amongst young people. Köbe finally suggests a steering instrument for political organisations to help them achieve these goals. In the book review section, we continue the theme of political participation and representation of the young. Simon Pistor reviews the book Youthquake 2017: The Rise of Young Cosmopolitans in Britain (Palgrave Macmillan, 2019) by James Sloam and Matt Henn. The book investigates youth political participation in Britain around and after the Brexit referendum in 2016 and is built around the new notion a “youthquake” – a term initially introduced by British media to describe the surprising success of the movement behind the Labour Party but later on also becoming Oxford Dictionaries’ 2017 word of the year. Pistor writes that Sloam and Henn expand the concept of a youthquake in their book to “youthquake elections” – “ones in which dramatic changes in how many young people vote, who they vote for and how active they are in the campaign have, quite literally, shaken up the status quo” (Sloam/Henn 2019: 8). Using this concept, the book’s central claim is that it was a youth movement based on a broader appeal to the needs of young people (especially by the Labour Party) which spiked the higher voter turnout among young people. Pistor’s review of the book is unequivocal: using methods from comparative politics, the authors provide a “very interesting argument” and “a clear empirical case for the youthquake during the 2017 General Election in the UK”. Pistor also welcomes especially two implications of the book: (1) many young British people are not as politically disenfranchised as general wisdom holds (and there is much more to be said about that); (2) many of them are not only cosmopolitans but also British cosmopolitans interested and engaged in national politics. Overall, Simon Pistor concludes that Sloam and Henn’s book is “an empirically rich and informed study”, which might suggest that the key to future democratic successes does indeed lie with the young.